PEMANFAATAN MEDIA BARU DALAM PENGGUNAAN ALTER EGO BAGI PENGGEMAR KOREAN POP (KPOP) - Rahman Gunawan; Cindy Christa Kharisma Reigen (Linimasa : Jurnal Ilmu Komunikasi, 2023)
The development of technology and information nowadays is very fast, especially in communication. The use of social media is increasingly mushrooming not only to interact and communicate but also to use social media as a manifestation of other personalities, one of which is what Korean pop (Kpop) fans do. They create a small community with fellow Korean pop idol group (Kpop) fans then use another name or the alter ego of each idol character he idolizes where they can mingle, communicate and even wage war between fans without knowing each other's real personal data because utilize new media to interact with each other. The purpose of this study is to conduct content analysis in what happens to the use of ego- counter accounts via the Twitter social media platform. In addition, the research method used is a descriptive qualitative approach, namely the analysis is carried out by interpreting messages or tweets on the Twitter platform by the alter ego account.